Сервис быстрых ответов от искусственного интеллекта
Вопрос пользователя:
Ответ нейросети:
To solve this inequality, we need to find the critical points where the expression is equal to zero and then determine the sign of the expression in each interval created by these critical points.
First, let's find the critical points by setting the expression equal to zero: x(6+x)(x-3/4) = 0
This expression will be equal to zero when x = 0, x = -6, and x = 3/4.
Now, let's test the expression in each interval created by these critical points:
Interval (-∞, -6): Choose x = -7: (-7)(-1)(-7-3/4) = (-7)(-1)(-31/4) = 217/4 > 0
Interval (-6, 0): Choose x = -1: (-1)(5)(-1-3/4) = (-1)(5)(-7/4) = 35/4 > 0
Interval (0, 3/4): Choose x = 1/2: (1/2)(6+1/2)(1/2-3/4) = (1/2)(13/2)(-1/4) = -13/16 < 0
Interval (3/4, ∞): Choose x = 1: (1)(7)(1-3/4) = (1)(7)(1/4) = 7/4 > 0
Therefore, the solution to the inequality x(6+x)(x-3/4) > 0 is x ∈ (-∞, -6) U (0, 3/4) U (3/4, ∞).
Напишите нам, если в вопросе есть ваши персональные данные (yasnoponyatno24@yandex.ru)
Обратите внимание: ответы, предоставляемые искусственным интеллектом, могут не всегда быть точными. Не рассчитывайте на них в критически важных областях, таких как медицина, юриспруденция, финансы или в вопросах, связанных с безопасностью. Для важных решений всегда обращайтесь к квалифицированным специалистам. Администрация сайта не несет ответственности за контент, сгенерированный автоматически.